THE ANALYSIS OF INTERPERSONAL MEANING (MOOD), IDEATIONAL MEANING (TRANSITIVITY) AND TEXTUAL MEANING (THEME) OF NEWS ITEM TEXT ENTITLED â€œNIKITA MIRZANI: I`M NOT A PROSTITUTEâ€ - Prawiro, Indra Yoga (Universitas Wiralodra, 2017)
Today, media has become primary needs as food and clothing. It has played significant role in strengthening the society that is as a